PENGARUH LITERASI KEUANGAN,PERILAKU KEUANGAN DAN PENDAPATAN TERHADAP KEPUTUSAN BERINVESTASI MAHASISWA FAKULTAS EKONOMI UNIVERSITAS MAHASARASWATI DENPASAR - Rosalia Dalima Landang; I Wayan Widnyana; I Wayan Sukadana (EMAS, 2021)
Investment constitutes sacrifice that is done on present moment with intent to get greater benefit at proximately (Haming and Basalamah, 2010). One of factor which is needed to do one investment is capital or fund. Source lents fund to get comes from peribadi's loan or fund. To the effect penelipian which is to know literasi's influence financially, financial behaviour, income for decision to get investment on Economic Faculty college student Mahasaraswati Denpasar's University. Total observational deep sample it as much 105 and by use of Formula Slovin. analisis's tech in observational it utilizes analisis bifilar linear regression, bifilar correlation, diterminasi, quiz t and quiz F. Result observationaling to point out Literasi finance (X1) having for positive and signifikan for decision to get investment (Y. ). Financial behaviour (X2) having for positive and signifikan for decision to get investment (Y. ). Income (X3) having for positive and signifikan for decision to get investment (Y. ). This result menunjukan that getting better Income Economic Faculty college student Mahasaraswati Denpasar's University therefore followed by decision step-up gets that investment. Literasi financially, financial behaviour and level propertied simultan's ala having for signifikan for decision to get Fkultas's College Student investment Mahasaraswati Denpasar's University Economy, iterasi's thus financially, financial behaviour and propertied have influence on level spontaneous gets investment.